2021
DOI: 10.1093/rheumatology/keab577
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and course of COVID-19 hospitalizations among patients with familial Mediterranean fever

Abstract: Objectives To evaluate the incidence of hospitalization for COVID-19 in patients with familial Mediterranean fever (FMF), as compared with the general population, and to compare the disease course between FMF inpatients, and age, sex, ethnicity, and comorbidity-matched non-FMF COVID-19 inpatients. Methods We used electronic medical records (EMR) to obtain data about the total number of the insured population and the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Metaanalyzes of observational and RCTs showed an advantage of colchicine use; however, subgroup analysis with randomized controlled trials showed no statistically significant difference in the mortality (OR: 0.80, 95%CI, 0.44-1.46) [101]. Moreover, colchicine neither prevented COVID-19-related hospital admissions nor disease course among rheumatic patients who were receiving it for their underlying diseases [102,103]. Colchicine has potential toxicities, particularly in those with kidney and liver impairment and elders, myelosuppression, elevation in transaminases, and myopathy, which are commonly observed during the course of COVID-19 [97,104].…”
Section: Colchicinementioning
confidence: 98%
“…Metaanalyzes of observational and RCTs showed an advantage of colchicine use; however, subgroup analysis with randomized controlled trials showed no statistically significant difference in the mortality (OR: 0.80, 95%CI, 0.44-1.46) [101]. Moreover, colchicine neither prevented COVID-19-related hospital admissions nor disease course among rheumatic patients who were receiving it for their underlying diseases [102,103]. Colchicine has potential toxicities, particularly in those with kidney and liver impairment and elders, myelosuppression, elevation in transaminases, and myopathy, which are commonly observed during the course of COVID-19 [97,104].…”
Section: Colchicinementioning
confidence: 98%
“…In addition, both colchicine and IL‐1 inhibitors treatments have recently been proposed for off‐label use in COVID‐19 patients 134,135 . However, another study did not observe any significant difference in the severity and outcome of COVID‐19 between FMF and non‐FMF patients 136 …”
Section: Future Perspectivesmentioning
confidence: 99%
“…134,135 However, another study did not observe any significant difference in the severity and outcome of COVID-19 between FMF and non-FMF patients. 136 Finally, it is important to emphasize that evidence to precisely guide the treatment in children with FMF is still limited and large multicentre clinical trials are definitely needed to improve the therapeutic management of paediatric FMF.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Finally, a small ( n = 36) retrospective case-control study from Jerusalem revealed that neither FMF history nor colchicine administration at baseline affected COVID-19-related length of hospitalization, mortality, oxygen support needs and mechanical ventilation [ 79 ].…”
Section: Colchicine and Covid-19 Infectionmentioning
confidence: 99%